Development of Arduino Uno Based Multispectra Colorimeter For Formaldehyde Determination - Anida, Choirun Nisa; Zulfikar, Zulfikar; Siswoyo, Siswoyo; Asnawati, Asnawati; Reza, Muhammad (Indonesian Chimica Letters, 2025)
Formalin is a hazardous substance that is often misused as a food preservative, so routine formalin analysis is very necessary for public safety. Formalin analysis generally uses spectrophotometry and also a simple colorimeter. Currently, many Arduino-based colorimeters are being studied and development with RGB (Red, Green, Blue) LED (Light Emitting Diode) light sources. This research is also in this field with a focus on the use of multi-spectral RGB LED lights with 16 colors that are already commercially available. The multispectral colorimeter is designed by integrating an LED light source, a photodiode module as a detector, and controlled by an Arduino Uno R3. The LED light module circuit, cuvette and detector photodiode are then arranged and packaged in an X8 project box. Optimization of the circuit is studied including the distance between the LED lamp and the cuvette and the photodiode with the cuvette. A feasibility study of the use of multispectral RGB LEDs is also carried out by looking at the stability of the response of each color. The performance test of the multispectral colorimeter is carried out by analyzing formaldehyde oxidized with hydrogen peroxide using methyl red as an indicator under the alkaline condition. The results showed no significant difference when viewed from the linearity, Limit of Detection, Limit of Quantitation, sensitivity, and precision values calculated from the calibration curve. The difference in linearity values was 0.0013, Limit of Detection = 0.17, Limit of Quantitation = 0.57, sensitivity = 0.0001, and precision (SD = 0.001 and %RSD = 0.11).